Molecular phylogeny of the freshwater fish family Cobitidae (Cypriniformes: Teleostei): delimitation of genera, mitochondrial introgression and evolution of sexual dimorphism - Slechtová, Vendula; Bohlen, Jörg; Perdices, Anabel (Molecular phylogenetics and evolution, 2008)
The family Cobitidae represents a characteristic element of the Eurasian ichthyofauna. Despite diverse features of sexual dimorphism, comparably few morphological characters have been utilized for taxonomic studies resulting in many unresolved puzzles. Here we present the phylogenetic relationships of Cobitidae as inferred from the mitochondrial cytochrome b gene and the nuclear gene RAG-1. Analyses of both markers show a group of eight nominal genera, which all occur in Europe and eastern, northern and western Asia, forming a monophyletic lineage (northern clade) while all other clades inhabit South and Southeast Asia (southern lineages). While all eight southern lineages correspond to genera as defined by morphological studies, only four lineages were reliably recovered within the northern clade, and of these only one (Sabanejewia) corresponds to a formerly considered genus. The genera Cobitis, Iksookimia and Niwaëlla were polyphyletic. A comparison of the two markers shows several incongruities within the northern clade and mitochondrial introgression at least in the genus Misgurnus. Mapping the characters of sexual dimorphism on our cladogram, we identified five character states that are diagnostic for certain lineages. Estimations of the divergence times dated the separation of the northern clade from the southern lineages to the middle Eocene (46 MYA) and the origin of "Cobitis"misgurnoides, the basal taxon of the northern clade, during early Oligocene (30-35 MYA). The geographic distribution of the major clades supports recently developed hypotheses about the river history of East Asia and further suggests that a range expansion of the northern clade in late Miocene (15 MYA) led to the colonisation of Europe by three already distinct genera.
Keywords: Animals; Europe; Asia; cytochromy b; Geography; Mitochondria; Bayesova věta; inbreeding; Evropa; máloostní; Bayes Theorem; Cytochromes b; Evolution, Molecular; molekulární evoluce; zeměpis; Sex Characteristics; mitochondrie; Fresh Water; Phylogeny; konsenzuální sekvence; sladká voda; Consensus Sequence; pohlavní dimorfismus; Asie; Inbreeding; Cypriniformes; zvířata; fylogeneze